PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENERIMAAN PAJAK PENGHASILAN DAN PAJAK PERTAMBAHAN NILAI - Herman (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
The purpose of this research is to find out the effect of economy growth toward tax collection, especially income tax andiralue added tax. The data covered from 1985 until 2005. Some variables included in this researdi such as: consumption, investment, government expenditure and import, and dependent variable is value added tax and income tax collection. The analyzing tools which used are nonnallytest, analyzing of variance, and goodness of fitand t-test. Result of analysis finds that the economy growth has significant effect to the income tax collection and value added tax collection.Keywords: Economic Growth, Gross Domestic Product, Income Tax, and Value Added Tax